Intelligent Shopping Agent - Shanbhag, Sameer; Nair, Sujith; Nai, Nikhil; Shaikh, Bushra (International Journal of Computer Sciences and Engineering, 2025)
Intelligent Shopping Agent is an Agent which helps user to browse online shops, compare prices and order merchandise sitting at home on their PC and get suggestions on what products are best suitable for them to buy and buy it at one click with an opportunity where the intelligent agents adds the products directly to the user cart. The interesting feature this website provides is price comparison and allowing the user to go buy goods from other website as well, without redirection this intern profits the user as they do not have to surf multiple website to find the best deal and the owner is profited as the users buy the products using their referral code.